Performance analysis of new energy-saving and environment-friendly materials for building decoration based on the whole life cycle - Zhiqiang Wu (Journal of Experimental Nanoscience)
As people put forward higher demand for the effect and quality of building interior decoration, the attention to building energy-saving materials has become higher and higher. In recent years, there have been many researches on green building energy-saving technology, green building evaluation and other aspects, but there are relatively few researches on applying the concept of full life cycle cost to the performance analysis of new materials for building energy conservation and environmental protection. Considering the economic performance of buildings will help to save resources in the construction industry and reduce energy consumption. The so-called full life cycle optimization of energy-saving design of green buildings is to take the concept of full life cycle optimization as the most reference, fully coordinate all elements in the portfolio project, and ensure that the full life cycle cost of the building can be greatly reduced. To realize the energy-saving optimization of green buildings, it is necessary to ensure that it runs through the whole life cycle of the building, fully combine the life cycle cost with the building function, and systematically do the optimization work. The performance analysis model of building decoration energy-saving and environmental protection new materials based on the whole life cycle proposed in this paper can be used to analyse the various properties of various new materials. The experimental results show that the maximum error of the test results is 9.6%, the minimum error is 1.3%, and the average error is only 6.43%. This shows that the model built in this paper is reliable, and the calculated results are in good agreement with the experimental results, which can be used to analyse the performance of new building decoration energy-saving and environmental protection materials. The ideas and methods of solving the model established in this paper have important guiding significance, and can be used as a powerful reference tool for studying other solving methods.